2019
DOI: 10.1126/sciadv.aax4249
|View full text |Cite
|
Sign up to set email alerts
|

Evolutionarily conserved regulation of sleep by epidermal growth factor receptor signaling

Abstract: The genetic bases for most human sleep disorders and for variation in human sleep quantity and quality are largely unknown. Using the zebrafish, a diurnal vertebrate, to investigate the genetic regulation of sleep, we found that epidermal growth factor receptor (EGFR) signaling is necessary and sufficient for normal sleep levels and is required for the normal homeostatic response to sleep deprivation. We observed that EGFR signaling promotes sleep via mitogen-activated protein kinase/extracellular signal–regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 33 publications
(43 citation statements)
references
References 70 publications
(163 reference statements)
0
41
0
Order By: Relevance
“…Third, colocalization analyses refined genetic effects previously described at the 198 KSR2 locus implicated in ERK/EGFR signaling 23 , a pathway with an established causal role in sleep regulation in C. elegans, Drosophila, and zebrafish 33,34 . This included an 200 intronic variant in KSR2, a gene that encodes a scaffold protein for ERK cascade signaling 35 Fifth, we found evidence of association for variants in PRRC2C, one of three 210 orthologs of the Drosophila nocte gene 36 .…”
Section: Napping Genetic Variants Share Causal Variants With Other Slmentioning
confidence: 71%
“…Third, colocalization analyses refined genetic effects previously described at the 198 KSR2 locus implicated in ERK/EGFR signaling 23 , a pathway with an established causal role in sleep regulation in C. elegans, Drosophila, and zebrafish 33,34 . This included an 200 intronic variant in KSR2, a gene that encodes a scaffold protein for ERK cascade signaling 35 Fifth, we found evidence of association for variants in PRRC2C, one of three 210 orthologs of the Drosophila nocte gene 36 .…”
Section: Napping Genetic Variants Share Causal Variants With Other Slmentioning
confidence: 71%
“…To verify that this stimulation paradigm indeed results in stimulation of NPVF neurons, we first tested Tg(npvf:ReaChR-mCitrine) ; Tg(npvf:GCaMP6s-tdTomato) animals (Lee et al, 2017; Lee et al, 2019). We first recorded baseline GCaMP6s fluorescence in npvf -expressing neurons, then optogenetically stimulated these neurons, and then recorded post-stimulation GCaMP6s fluorescence in these neurons ( Figure 2 – figure supplement 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…The hypothalamic-hindbrain neuronal circuit that we have described can be integrated into a larger sleep-promoting network. We recently reported that epidermal growth factor receptor (EGFR) signaling is necessary and sufficient for normal sleep amounts in zebrafish, and that it promotes sleep, in part, via the NPVF system (Lee et al, 2019). We found that it does so by both promoting the expression of npvf and by stimulating npvf -expressing neurons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other possible Pum functions that could have played a role in our results include EGFR and the regulation of inflammatory pathways. EGFR is a direct target of Pum in Drosophila and has been implicated in sleep regulation in flies, worms, zebrafish and humans (Foltenyi et al, 2007;Kim et al, 2012;Lee et al, 2019;Konietzka et al, 2020). These studies showed that EGFR signaling promotes sleep in all organisms tested but its role in sleep homeostasis was only examined in zebrafish.…”
Section: Discussionmentioning
confidence: 99%